Peran Akad Pembiyaan Murabahah Terhadap Perkembangan Ekonomi Ummat Dalam Bidang UMKM - Ananda, Lili Permata; J, Julina; H, Herlinda (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The role of sharia banking through murabahah financing is to make it easy for UMKM to develop their businesses through business capital. This research aims to find out whether murabahah financing plays a role in the economic development of the ummah in the MSME sector. This research uses a literature study or library research method. The results of the research show that murabahah contract financing is very influential, as shown by several journal data and previous research which discusses murabahah contract financing.